1987
DOI: 10.1152/jappl.1987.63.2.558
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional responses to prolonged hindlimb suspension in rat muscle

Abstract: The purpose of this study was to investigate alterations in structural and functional properties in the soleus (SOL) and extensor digitorum longus (EDL) muscles of rats after 1, 2, and 5 wk of tail suspension. Maximal O2 uptake was 19% lower after 5 wk suspension. Loss of muscle mass was greater in SOL (63%) than in EDL (22%) muscle. A reduction of type I distribution was accompanied by an increase of intermediate fiber subgroups (int I in SOL, int II in EDL). The cross-sectional area of all three fiber types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
126
2
3

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(154 citation statements)
references
References 0 publications
23
126
2
3
Order By: Relevance
“…In Desplanches et al (3) results, the animals presented a higher loss of weight during the first days of suspension but, after fourteen days, most of them restored the lost weight.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In Desplanches et al (3) results, the animals presented a higher loss of weight during the first days of suspension but, after fourteen days, most of them restored the lost weight.…”
Section: Discussionmentioning
confidence: 86%
“…Nos resultados de Desplanches et al (3) , os animais tiveram maior perda de peso nos primeiros dias de suspensão mas, após quatorze dias, a maioria deles recuperou o peso perdido.…”
Section: Discussionunclassified
“…The suspended rats were able to use forelimbs to move around a pivot, permitting access to food and water freely. Apparent changes in the structure and function of muscle fibers after 2-week suspension have been reported (DESPLANCHES et al, 1987;ELDER and MCCOMAS, 1987). Therefore, we decided that a period of 2-week suspension hypokinesia in this study would be appropriate.…”
Section: Methodsmentioning
confidence: 98%
“…Some studies have reported that unloading causes oxidative stress such as overexpression of reactive oxygen species, leading to capillary regression in the atrophied muscle 15,16) . Although elevation of reactive oxygen species was not observed in the present study, the overexpression of reactive oxygen species has been shown in similarly atrophied muscles in other studies 4,5) , and in the present study, atrophied plantaris muscle may have been exposed to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%